INTEGRATING SPIRITUAL VALUES INTO EDUCATIONAL LEADERSHIP TO FOSTER THE FUTURE GENERATION - Hartinah, Hartinah; Maulana, Robi Hilmy; A, Yuliana (Universitas Islam Kiai Haji Achmad Siddiq Jember, 2025)
Education plays a crucial role in shaping the character and quality of future generations. As the world advances with the challenges of globalization and technological development, educational leadership faces increasingly complex dynamics. One of the key aspects is the integration of spiritual values in educational leadership to create a generation that is not only intellectually intelligent but also morally upright and strong in character. This study aims to comprehensively explore the importance of integrating spiritual values in educational leadership to develop a responsible and character-driven future generation. By incorporating spiritual values, the educational system is designed not only to focus on academic achievement but also on moral and ethical development. This research employs a qualitative approach with a literature study by analyzing and selecting relevant sources, such as articles, books, and research reports, related to the integration of spiritual values in leadership. The findings indicate that spiritually-based educational leadership can serve as a strategic solution to global challenges, producing a generation that excels academically while also possessing strong emotional and moral maturity. Therefore, the integration of spiritual values in educational leadership should be continuously developed to contribute to building a future generation with strong character and integrity